2017
DOI: 10.1038/s41598-017-00666-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the spatio-temporal dynamics of rotifer community structure based on taxonomic indices and functional groups in two subtropical lakes

Abstract: Little research has focused on how rotifer communities respond to eutrophication based on their combined taxonomic and functional indices. In this research, the relationship of the environment and rotifer communities was comparatively investigated in two subtropical lakes over one year. The taxon-based indices, including species number (S), Margalef index (D), Simpson index (d), Shannon-wiener index (H′), and functional traits relying on the guild ratio (GR) and the modified guild ratio (GR′) from the moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
3
13
0
2
Order By: Relevance
“…The last possible reason could be environmental factors. Studies have shown that change in physico-chemical factors such as nutrients, pH, turbidity and temperature can affect rotifer community structure (Armengol et al 1998;Duggan et al 2002;Wen et al 2017). Changes in rotifer community structure could in turn lead to wavering of foodwebs and stability of the wetland lake.…”
Section: Seasonal Variation Of Zooplankton Functional Groups Biomassmentioning
confidence: 99%
“…The last possible reason could be environmental factors. Studies have shown that change in physico-chemical factors such as nutrients, pH, turbidity and temperature can affect rotifer community structure (Armengol et al 1998;Duggan et al 2002;Wen et al 2017). Changes in rotifer community structure could in turn lead to wavering of foodwebs and stability of the wetland lake.…”
Section: Seasonal Variation Of Zooplankton Functional Groups Biomassmentioning
confidence: 99%
“…For example, in nature, one or more genera such as Anuraeopsis, Keratella, Kellicottia, Brachionus, Polyarthra, Liliferotrocha, Trichocerca, Synchaeta, Cephalodella, Conochilus, Lepadella, Lecane and Ptygura often become highly abundant. They reach >1 ind mL -1 , at least in certain seasons (Duggan et al, 2002;Smith et al, 2009;Nandini et al, 2016;Wen et al, 2017). On the other hand, certain other rotifer genera such as Tripleuchlanis, Cyrtonia, Microcodides, Tetrasiphon, Lindia and Asplanchna rarely exceed 500 ind L -1 (Fontaneto and Melone, 2003;Wallace et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our data on the TSI showed no clear relation between this index and the Shannon–Wiener diversity index. It has been reported that microphages dominate under eutrophic conditions and raptorial rotifers dominate in bodies of water with low TSI (Ŝpoljar, Tomljanović, & Lalić, ; Wen, Zhai, Feng, Yang, & Xi, ). However, in our study the opposite was observed: raptorial sessile rotifers dominated during much of the year.…”
Section: Discussionmentioning
confidence: 99%